2009
DOI: 10.1377/hlthaff.28.4.w751
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Childhood Obesity On Hospital Care And Costs, 1999–2005

Abstract: Childhood obesity is increasingly recognized as an epidemic, but the economic consequences have not been well quantified. We evaluated trends in obesity-associated hospitalizations, charges, and costs using 1999-2005 data from a nationally representative sample of admissions to U.S. hospitals. We detected a near-doubling in hospitalizations with a diagnosis of obesity between 1999 and 2005 and an increase in costs from $125.9 million to 237.6 million (in 2005 dollars) between 2001 and 2005. Medicaid appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 25 publications
(20 reference statements)
0
103
0
4
Order By: Relevance
“…Pediatric hospitalizations for obesity-related conditions have doubled in the last decade, mirroring the trend of higher levels of childhood obesity in the United States. [1][2][3] Recent studies have demonstrated worsened pediatric in-hospital outcomes, including mortality and increased resource utilization, for children with obesity across a range of diagnoses. [4][5][6][7][8][9][10] Although the mechanisms driving the association between obesity and in-hospital outcomes are not fully known, for asthma it is believed that adipocytes expressing inflammatory markers create a low level of systemic inflammation, thereby increasing the severity of allergic-type illnesses and decreasing the response to anti-inflammatory medications, such as steroids.…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric hospitalizations for obesity-related conditions have doubled in the last decade, mirroring the trend of higher levels of childhood obesity in the United States. [1][2][3] Recent studies have demonstrated worsened pediatric in-hospital outcomes, including mortality and increased resource utilization, for children with obesity across a range of diagnoses. [4][5][6][7][8][9][10] Although the mechanisms driving the association between obesity and in-hospital outcomes are not fully known, for asthma it is believed that adipocytes expressing inflammatory markers create a low level of systemic inflammation, thereby increasing the severity of allergic-type illnesses and decreasing the response to anti-inflammatory medications, such as steroids.…”
Section: Resultsmentioning
confidence: 99%
“…The direct costs of childhood obesity include annual prescription drug, emergency room, and outpatient costs of $14.1 billion, 29 plus inpatient costs of $237.6 million. 30 An even larger cost is incurred when obese children become obese adults. About a third of obese preschool children, and about half of obese school-age children, become obese adults.…”
Section: Economic Consequences Of Childhood Obesitymentioning
confidence: 99%
“…D.H.H.S., 2010), that significantly raise health care costs for youth (Trasande and Chatterjee, 2009;Trasande, Liu, Fryer et al, 2009). (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%